PENGARUH AKTIVITAS OLAHRAGA TERHADAP TINGKAT KEBUGARAN JASMANI SISWA - Otniel Zega; Alfandi Arya; Bangun Hotmatua Simamora; Adinda Natasya; Nimrot Capello Manalu (STKIP Subang, 2026)
Physical fitness is one of the important factors that supports students’ health and daily activities. Students with good physical fitness can perform activities effectively without experiencing excessive fatigue. In today’s modern lifestyle, many students spend more time using electronic devices and doing less physical activity, which can reduce their level of physical fitness. Therefore, sports activities play an essential role in improving and maintaining students’ physical fitness. Sports activities such as running, football, badminton, basketball, and aerobic exercise help improve muscle strength, body flexibility, heart and lung function, and overall endurance. Students who participate regularly in sports activities generally have better stamina and stronger physical endurance than those who rarely exercise. In schools, physical education subjects provide opportunities for students to engage in physical activities that support a healthy lifestyle. Regular exercise not only improves physical health but also contributes positively to mental health by reducing stress, increasing concentration, and improving self-confidence. Several studies have shown that students who exercise consistently tend to have higher physical fitness levels because the frequency, intensity, and duration of exercise greatly influence physical performance. Students who exercise at least three times a week often show better cardiovascular endurance, muscle strength, and body coordination. In contrast, lack of physical activity may increase the risk of obesity, fatigue, and other health problems. Therefore, sports activities have a significant positive influence on students’ physical fitness levels and should be encouraged both in school and daily life to create healthier, more active, and more productive students.